2019
DOI: 10.5430/afr.v8n4p144
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance and Sustainability of Moroccan Microfinance Institutions: An Empirical Study

Abstract: This study explores the determinants of the financial performance and sustainability of Moroccan Microfinance Institutions (MFIs). Through the use of panel data concerning 10 MFIs (available on the MIX platform) with different time frames, three OLS models are run and aim to explain MFIs financial performance and sustainability using independent variables related to the size of the MFIs, the quality of their loan portfolios, the degree of outreach, and their productivity. The results obtained show that: (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Results indicate that staff productivity significantly and positively impacts the profitability and sustainability of these microfinance institutions. This aligns with the contribution of Aguenaou et al (2019), as the authors found a significant impact using OLS regression of the loan per staff member on ROE, ROA, and OSS. In addition to that, El Kharti (2014) confirms the same relationship between staff productivity, ROA and ROE.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Results indicate that staff productivity significantly and positively impacts the profitability and sustainability of these microfinance institutions. This aligns with the contribution of Aguenaou et al (2019), as the authors found a significant impact using OLS regression of the loan per staff member on ROE, ROA, and OSS. In addition to that, El Kharti (2014) confirms the same relationship between staff productivity, ROA and ROE.…”
Section: Discussionsupporting
confidence: 79%
“…The literature highlights the importance of the use of metrics that includes ROA, ROE, and OSS to measure these institutions' performance. While the number of contributions that assess the determinants of Moroccan MFIs is limited (El Kharti, 2014;Aguenaou et al, 2019), the following paper distinguishes itself in the current literature in two ways. First, the use of the structural equation modelling that allows the use of endogenous and exogenous variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations